PEMBELAJARAN MAHARAH QIRO’AH BAHASA ARAB PADA SISWA KELAS XI IPA 7 MADRASAH ALIYAH NEGERI 2 KOTA BIMA (STUDI KASUS MAN 2 KOTA BIMA) - Umar, Misba; Zuriyah, Nurul; Wahyuningsih, Sri (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
Based on the initial observations of researchers in class XI IPA 7 Madrasah Aliyah Negeri 2 bima city, that learning maharah qiro'ah using learning methods that are quite varied, because students get bored quickly with learning, lack of learning motivation, and uneven Arabic language skills. So that this research aims to find out the Learning of Maharah Qiro'ah Arabic Language in Class Xi Ipa 7 Madrasah Aliyah Negeri 2 Kota Bima (Case Study Man 2 Kota Bima). This research will be conducted at Madrasah Aliyah Negeri 2 Kota Bima West Nusa Tenggara. This research uses Qualitative Research with a Case Study Approach. Data collection techniques are observation, interview and documentation. Data Analysis Techniques are Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of this study that students progressed in Arabic reading skills, but the difference in the level of ability between students became one of the main obstacles in the learning process. Some students who already have a good foundation of Arabic can feel unchallenged, while other students who are just starting to learn Arabic have difficulty in reading and understanding texts quickly and precisely.